Examining National Incident-Based Reporting System (NIBRS) Data: Perspectives From a Quarter Century of Analysis Efforts. (December 2015) - Jarvis, John P.
The National Incident-Based Reporting System (NIBRS) has been a repository for crime data for almost 25 years. This work explores the uses and applications of these data to shed light on a variety of crime and policing issues since the data became available in the early to mid 1990s. Specific attention and discussion is devoted to some of the advances that NIBRS data affords as well as some of the limitations that have been discovered. Documenting both the challenges and opportunities that NIBRS data have provided was the aim of this work. Both the research and practice communities can profit from further data collection and analysis of this important source of information relative to crimes that become known to the police.